Health and cleanliness : a text book for teachers - Green, George H. (George Henry), 1881- ; Buchan, G. F.; Muir, W. A. (London : Health and Cleanliness Council)
1938-03 1938 1930s 69 pages : illustrations SECOND GROUP OF LESSONS CLEANLINESS OF HEAD, TEETH, AND NOSE SYLLABUS Toilet of Head. — Brushing and combing the hair. Need for use of clean comb and brush, kept for own use. How to clean the brush and comb. Washing the hair. Advantage of short hair. Headgear. — Importance of cleanliness of headgear, and of wearing own headgear. Advantages of wearing no hat, especially in summer. Some of the results of inattention to these rules: diseased condition of scalp, loss of hair, etc.; communication of head diseases and transmission of parasites. Toilet of Mouth and Teeth. — Brushing of teeth after every meal and thorough cleansing before retiring at night. Rinsing of the mouth on rising. Cleanliness of the toothbrush. Toilet of Nose. — The use of the handkerchief. Importance of keeping nasal channels clear, to prevent mouth-breathing, adenoids, and colds, etc. Cleanliness of the handkerchief — need for frequent washing and for use of own handkerchief. Method of breathing. The placing of the hand or handkerchief over the mouth when sneezing or coughing. Why we should not spit. How expectoration should be dealt with. NOTES ON METHOD The "reasons why" of the majority of the habits discussed in this section demand some understanding of the germ theory for their proper appreciation. Neverthe- 23 177/5/8/3